(untitled)
The purpose of this study was to determine the effect of work motivation, competence and compensation on the performance of insurance agents at the Mandiri Cakra Ning Nusa Marketing Office of PT Sun Life Denpasar. The population is all 97 insurance agents at the Mandiri Cakra Ning Nusa Marketing Office of PT Sun Life Denpasar, so the census method is used. The method of data collection uses questionnaires, observations, interviews and documentation studies. The data analysis techniques used are Multiple Linear Regression Analysis, determination coefficient analysis, Significant test t and Significant test F. Results of this study are 1) T value calculate variable work motivation = 2.458, significant value is 0.016